Trade policy impacts on net wheat importers in the CIS: Three essays - Nurzat Baisakova (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
[Objectives of the study] The general question emphasized in this work is how the global food crisis during 2008-2011 and frequent grain export restrictions by the major exporters of this commodity affected the net wheat importing countries of Central Asia (Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) and the Caucasus (Armenia, Azerbaijan, and Georgia). The aim of this dissertation is to study the impacts of such trade policies on the net grain importing countries of the CIS by focusing on three selected issues of this research problem. Each essay represents a separate work with its own research question, theories, methodology, and data. These research questions are, however, related to the general research question above and represent an analysis of the involved parties at three levels: international - the analysis of grain trade among several states, national - the analysis of the intermediate flour suppliers, and the micro-level - the analysis of households. [Contents] 1 Russia's wheat trade policy with its neighbors: The neorealism perspective - 2 Agribusiness in transition: Insights from structural change in grain processing in Central Asia - 3 Quantitative analysis of heterogeneus effects of grain export policies on Kyrgyz wheat producers and consumers.
urn:nbn:de:gbv:3:2-86084
Keywords: 330